Enhanced immobilization of U(VI) using a new type of FeS-modified Fe0 core-shell particles - Duan, Jun; Ji, Haodong; Liu, Wen; Zhao, Xiao; Bing Han; Tian, Shuting; Zhao, Dongye (Chemical Engineering Journal, 2019)
Sulfur-modified zero valent iron (S-ZVI) particles have been reported to show improved reactivity and selectivity than conventional ZVI. However, current methods for ZVI sulfidation do not fully utilize the advantages of the material, and S-ZVI has not been tested for U(VI) immobilization. In this work, we synthesized a new type of FeS-modified ZVI core-shell particles (FeS@Fe0) through a facile two-step reaction approach, and then tested for reductive sequestration of U(VI) in water. X-ray diffraction, Scanning transmission electron microscopy, and physical property analyses confirmed the formation of the core-shell structure, surface compositions and magnetic properties. Batch kinetic tests showed that FeS@Fe0 with an Fe0/FeS molar ratio of 1:1 offered the highest U(VI) reduction rate, prolonged reactive life than pristine ZVI, and the reduced uranium was most resistant to re-oxidation when exposed to oxygen. The retarded first-order kinetic model was able to adequately interpret the experimental rate data. FeS@Fe0 performed well over the pH range 5.5–9.0, with higher pH more favoring the reaction. High concentrations (5–10 mg/L) of humic acid, bicarbonate (1–5 mM) and Ca2+ (1 mM) showed only modest inhibition to the U(VI) reduction. Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and extraction studies indicated that U(VI) was immobilized via both direct adsorption and reductive precipitation, where Fe0 was the main electron source, with Fe0, sorbed Fe(II) and structural Fe(II) acting as the electron donors. FeS@Fe0 may serve as an improved material for efficient immobilization of U(VI) and other redox-active contaminants in water.
Keywords: Iron sulfide; Radionuclide; Reductive immobilization; Sulfidated iron; Uranium removal; Zero valent iron